Tax Administration versus Tax Rates: Evidence from Corporate Taxation in Indonesia - Basri, M. Chatib; Felix, Mayara; Hanna, Rema; Olken, Benjamin A. (American Economic Review, 2021)
We compare two approaches to increasing tax revenue: tax administration and tax rates. We show that when Indonesia moved top regional firms into “medium taxpayer offices,” with high staff-to-taxpayer ratios, tax revenue more than doubled. Examining nonlinear changes to corporate income tax rates, we estimate an elasticity of taxable income of 0.579. Combining these estimates, improved tax administration is equivalent to raising top rates on all firms by 8 percentage points. On net, improved tax administration can have significant returns for developing countries. (JEL H25, H26, K34, O17)